Microsoft Intune Cookbook Over 75 Recipes for Configuring, Managing, and Automating Your Identities, Apps, and Endpoint Devices - Taylor, Andrew (Packt Publishing Ltd., 2023)
Get started with Microsoft Intune and explore its many facets, including task automation with Microsoft Graph Key Features Create and configure your new mobile device management (MDM) environment Become an Intune pro by mastering compliance policies, monitoring techniques, reporting practices, and application deployment procedures Learn how to manage Windows, Android, iOS, and macOS devices using Intune Purchase of the print or Kindle book includes a free PDF eBook Book Description Microsoft Intune is a cloud-managed mobile device management (MDM) tool that empowers you to manage your end-user device estate across various platforms. While it is an excellent platform, the initial setup and configuration can be a daunting process, and mistakes made early on can be more challenging to resolve later. This book addresses these issues by guiding you through the end-to-end configuration of an Intune environment, incorporating best practices and utilizing the latest functionalities. In addition to setting up your environment, you'll delve into the Microsoft Graph platform to understand the underlying mechanisms behind the web GUI. This knowledge will enable you to automate a significant portion of your daily tasks using PowerShell. By the end of this book, you'll have established an Intune environment that supports Windows, Apple iOS, Apple macOS, and Android devices. You'll possess the expertise to add new configurations, policies, and applications, tailoring an environment to your specific requirements. Additionally, you'll have the ability to troubleshoot any issues that may arise and package and deploy your company applications. Overall, this book is an excellent resource for anyone who wants to learn how to use Microsoft Intune to manage their organization's end-user devices. What you will learn Set up your Intune tenant and associated platform connections Create and deploy device policies to your organization's devices Find out how to package and deploy your applications Explore different ways to monitor and report on your environment Leverage PowerShell to automate your daily tasks Understand the underlying workings of the Microsoft Graph platform and how it interacts with Intune Who this book is for This book is for IT professionals, end-user device administrators, and system administrators looking to transition to cloud-managed devices or enhance their current environment.
Description based upon print version of record. - Configuring enrollment profiles
Keywords: Electronic data processing -- Distributed processing; Information resources management; Business -- Data processing; Application software; Management -- Data processing; Traitement réparti; Gestion de l'information; Gestion; Informatique; Logiciels d'application